Democracy and Reforms : Evidence from a New Dataset - Spilimbergo, Antonio (IMF Working Papers; Working Paper ;, 2010)
Empirical evidence on the relationship between democracy and economic reforms is limited to few reforms, countries, and years. This paper studies the impact of democracy on the adoption of economic reforms using a new dataset on reforms in the financial, capital and banking sectors, product markets, agriculture, and trade for 150 countries over the period 1960 - 2004. Democracy has a positive and significant impact on the adoption of economic reforms but there is no evidence that economic reforms foster democracy. Our results are robust to the inclusion of a large variety of controls and estimation strategies.